Biodiversity hotspots distribution and protection of conservation priority areas - Zachos, Frank E.; Habel,Jan Christian; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Biodiversity and its conservation are among the main global topics in science and politics and perhaps the major challenge for the present and coming generations. This book written by international experts from different disciplines comprises general chapters on diversity and its measurement, human impacts on biodiversity hotspots on a global scale, human diversity itself and various geographic regions exhibiting high levels of diversity. The areas covered range from genetics and taxonomy to evolutionary biology, biogeography and the social sciences. In addition to the classic hotspots in the tropics, the book also highlights various other ecosystems harbouring unique species communities including coral reefs and the Southern Ocean. The approach taken considers, but is not limited to, the original hotspot definition sensu stricto and presents a chapter introducing the 35th hotspot, the forests of East Australia. While, due to a bias in data availability, the majority of contributions on particular taxa deal with vertebrates and plants, some also deal with the less-studied invertebrates. This book will be essential reading for anyone involved with biodiversity, particularly researchers and practitioners in the fields of conservation biology, ecology and evolution.
Global biodiversity conservation : the critical role of hotspots / Russell A. Mittermeier ... [et al.] -- A tough choice : approaches towards the setting of global conservation priorities / Christine B. Schmitt -- Quantifying biodiversity : does it matter what we measure? / T. Jonathan Davies and Marc W. Cadotte -- Human population and the hotspots revisited : a 2010 assessment / John N. Williams -- Vascular plant diversity in a changing world : global centres and biome-specific patterns / Jens Mutke ... [et al.] -- Genetic basis of human biodiversity : an update / Guido Barbujani and Vincenza Colonna -- Mediterranean peninsulas : the evolution of hotspots / Godfrey M. Hewitt -- Global change effects on Alpine plant diversity / Georg Grabherr, Michael Gottfried, and Harald Pauli -- European hotspots as evidenced by the Palearctic distribution of songbirds / Ronald Sluys, Mansour Aliabadian, and Cees S. Roselaar -- Patterns and hotspots of carabid beetle diversity in the Palaearctic : insights from a hyperdiverse invertebrate taxon / Andreas Schuldt and Thorsten Assmann -- The Carpathians as a major diversity hotspot in Europe / Miklós Bálint ... [et al.] -- Conservation in a biodiversity hotspot : insights from cultural and community perspectives in Madagascar / Nadine V.M. Fritz-Vietta ... [et al.] -- The kingdom of the frogs : anuran radiations in Madagascar / Philip-Sebastian Gehring ... [et al.] -- Hotspots, conservation, and diseases : Madagascar?s megadiverse amphibians and the potential impact of chytridiomycosis / Stefan Lötters ... [et al.] -- Impacts of biofuel expansion in biodiversity hotspots / Janice S.H. Lee, John Garcia-Ulloa, and Lian Pin Koh -- Forests of east Australia : the 35th biodiversity hotspot / Kristen J. Williams ... [et al.] -- Status and threats in the dynamic landscapes of northern Australia?s tropical rainforest biodiversity hotspot : the wet tropics / Nigel E. Stork, Steve Goosem, and Stephen M. Turton -- Explosive speciation and adaptive radiation of East African cichlid fishes / Christian Sturmbauer, Martin Husemann, and Patrick D. Danley -- Inter- and intraspecific genetic biodiversity in South East Asian rodents : new insights for their conservation / Marie Pagès, Alice Latinne, and Michaux Johan -- The amphibians and reptiles of Sulawesi : underestimated diversity in a dynamic environment / André Koch -- The Brazilian Atlantic forest : a shrinking biodiversity hotspot / Milton Cezar Ribeiro ... [et al.] -- Sustainable development and conservation of biodiversity hotspots in Latin America : the case of Ecuador / Marco Rieckmann ... [et al.] -- When hotspots meet : the Galápagos Islands : a hotspot of species endemism based on a volcanic hotspot centre / Sebastian Steinfartz -- Hotspots on global coral reefs / Marjorie L. Reaka and Sara A. Lombardi -- Biodiversity of a unique environment : the Southern Ocean benthos shaped and threatened by climate change / Angelika Brandt and Julian Gutt -- Biodiversity hotspots : concluding remarks and perspectives / Frank E. Zachos, Russell A. Mittermeier, and Jan C. Habel.
Electronic reproduction.
Keywords: Biodiversity conservation; Ecosystem management; Protected areas; Endangered species; Biogeography; Electronic books